Crystal Structure of Streptococcus pyogenes Csn2 Reveals Calcium-Dependent Conformational Changes in Its Tertiary and Quaternary Structure - Koo, Yoon; Jung, Du-kyo; Bae, Euiyoung (PLOS ONE, 2012)
Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated (Cas) proteins constitute a microbial immune system against invading genetic elements, such as plasmids and phages. Csn2 is an Nmeni subtype-specific Cas protein, and was suggested to function in the adaptation process, during which parts of foreign nucleic acids are integrated into the host microbial genome to enable immunity against future invasion. Here, we report a 2.2 Å crystal structure of Streptococcus pyogenes Csn2. The structure revealed previously unseen calcium-dependent conformational changes in its tertiary and quaternary structure. This supports the proposed double-stranded DNA-binding function of S. pyogenes Csn2.